Photooxidation and quantum confinement effects in exfoliated black phosphorus - Favron, Alexandre; Gaufrès, Etienne; Fossard, Frédéric; Phaneuf-L’Heureux, Anne-Laurence; Tang, Nathalie Y-W.; Lévesque, Pierre L.; Loiseau, Annick; Leonelli, Richard; Francoeur, Sébastien; Martel, Richard (Nature materials, 2015)
Thin layers of black phosphorus have recently raised interest owing to their two-dimensional (2D) semiconducting properties, such as tunable direct bandgap and high carrier mobilities. This lamellar crystal of phosphorus atoms can be exfoliated down to monolayer 2D-phosphane (also called phosphorene) using procedures similar to those used for graphene. Probing the properties has, however, been challenged by a fast degradation of the thinnest layers on exposure to ambient conditions. Herein, we investigate this chemistry using in situ Raman and transmission electron spectroscopies. The results highlight a thickness-dependent photoassisted oxidation reaction with oxygen dissolved in adsorbed water. The oxidation kinetics is consistent with a phenomenological model involving electron transfer and quantum confinement as key parameters. A procedure carried out in a glove box is used to prepare mono-, bi- and multilayer 2D-phosphane in their pristine states for further studies on the effect of layer thickness on the Raman modes. Controlled experiments in ambient conditions are shown to lower the A g 1 /A g 2 intensity ratio for ultrathin layers, a signature of oxidation. The degradation of exfoliated black phosphorus in ambient conditions may limit its use in electronic devices. The combined effects of light irradiation and exposure to oxygen on mono- and multilayers of this material are now investigated.